Avaliando a relação existente entre os escopos de requisitos e código: um estudo envolvendo sistemas em evolução - Silva Filho, José Renato da (Universidade Federal Rural do Semi-Árido, 2017)
Software systems are constantly changing during their evolution. These changes are directly linked with the management of their product requirements. When requirements are well managed, they evolve more accurately and development costs are reduced, which includes avoiding unnecessary changes to evolving code. It is known that much of the changes demanded during the evolution of the code is associated with the scope of its elements. However, there are no studies investigating whether variations in the scope of requirements are correlated with variations in the scope of code compositions. The main purpose of this master’s thesis is to provide means to requirements engineers to monitor variation in the scope of software requirements and to correlate them with the scope of evolving code elements, which has a proven negative impact on the number of changes demanded in evolving code artifacts. In this context, a metric was formulated to quantify the scope of requirements and based on it a plug-in, called MeRS, was developed. MeRS provides means to automate this quantification. Using MeRS, an exploratory study was conducted to correlate the scopes at the requirements and code levels. To do so, we analyze the evolution of the requirements and code, focusing on the scope of two applications in evolution: NotePad and Mobile Media. The results showed that the requirements scope values are correlate with the scope of the code
Keywords: Software em evolução; Requisitos de software; Escopo; Software evolution; Software requirement; Scope; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO